Prospects and Challenges of Crowdfunding as an Alternative Funding Option in Nigeria - Aderemi, Abdulmajeed M.R.; Maulida, Sri; Maikabara, Abdullateef Abdulqadir (IAIN Salatiga, 2021)
This study aims to review the concept, prospects, and challenges of crowdfunding in Nigeria.Â Furthermore, it adopts a library-based concept in which secondary sources are relied on dataÂ collection using descriptive and deductive approaches of analysis. The results showed thatÂ Nigeria has the potential of becoming the hub center of crowdfunding in Africa. However,Â various challenges are facing the growth of this platform as a means of ï¬nancing. TheseÂ include the issues of regulation, lack of adequate awareness, as well as fraud and corruption.Â Furthermore, this study recommends the need for adequate awareness about crowdfundingÂ and the regulation to ensure its functionality. It also oï¬€ers additional literature as a means ofÂ ï¬nancing, especially from the Nigerian context.